(untitled) (TSUL LEGAL REPORT, 2026)
This article provides descriptions of evidence and proof in criminal proceedings. At the pre-trial stage and in court, the admissibility of the evidence and the issues raised were raised. Procedures for the collection and examination of evidence are explained. The question of whether or not to admit the evidence to the court has been clarified. The subjects of evidence and their powers in conducting investigative actions are also explained. The purpose and subject of the proof are specified in a separate order with clear criteria. A comparative legal analysis of prejudicial issues in the criminal procedure law of the CIS countries, scientific proposals and recommendations on the implementation of the national legislation on the application of the institution of prejudice in criminal procedure law in the Republic of Uzbekistan and the development of the legal framework of this institution. The relevance of the topic is that in the criminal process, the institution of prejudice allows to resolve conflicts in the activities of state bodies and officials responsible for criminal proceedings, to easily resolve prejudicial situations that require a lot of money and effort. The object of research is the legal relationship arising from the application of the institution of prejudice in criminal proceedings. The subject of research is the objective laws of activity on the implementation of the institution of prejudice in law, sources of national and foreign criminal procedure legislation.